Efficacy of Stem /Steam /Metals as Comprehensive Strategies in Sri Lanka Education System - Abi Huraira Rifas; M.M. Sithy Fathima; K.R. Fathima Seefa (DIROSAT: Journal of Education, Social Sciences & Humanities, 2025)
Education encompasses the integration of knowledge, attitudes, skills, practice, and experiences. The concept of education has undergone evolutionary changes over time, influenced by educational policies and their intersection with political dynamics. This study aims to study the significance of Science, Technology, Engineering, Mathematics, Aesthetic, and Language (STEM/STEAM/METALS) strategies in transforming the education system. This research employs the documentary analysis technique that uses circulars, books, handbooks and guides as secondary data. The primary concerns impacting the economy and development of Sri Lanka include job dissatisfaction, inadequate income, unemployment, and a workforce lacking in necessary skills. Hence there is an urgent need for expertly formulated reforms and ideas in the sphere of education, specifically focusing on Science, Technology, Engineering, Aesthetic, and Mathematics from grade 01 to grade 13, as well as in higher education. This article provides an overview of the STEAM background, educational challenges, and the existing syllabus and curriculum for primary, junior secondary, senior secondary, and advanced level education. It also compares the Ministry of Education's (MOE) proposal for Science, Technology, Engineering, and Mathematics (STEM) with the policy reforms suggested by the National Education Commission (NEC). In recent years, it is anticipated that there will be an emergence of new educational trends in Sri Lanka, driven by the innovative perspectives of the current government. These trends are expected to contribute to the nation's progress and prosperity through an enhanced focus on education in the soon future.